New Australasian Parathalassiinae (Diptera: Dolichopodidae sensu lato) - Brooks, Scott E.; Cumming, Jeffrey M. (Zootaxa, 2022)
One species of Chimerothalassius Shamshev & Grootaert, namely C. marshalli sp. nov. is described from New Zealand, and two other species, namely C. riparius sp. nov. and C. sinclairi sp. nov. are described from New Caledonia. Two species of Microphorella Becker, namely M. bungle sp. nov. and M. viticula sp. nov., are described from Australia. These new parathalassiine descriptions increase the Australasian species diversity of Chimerothalassius and Microphorella to four species each. In addition, the genus Eothalassius Shamshev & Grootaert is recorded from New Caledonia based on a single female, and the male genitalia of the Australian species M. iota Colless is newly illustrated. A key to the genera and species of male Parathalassiinae in the Australasian Region is also provided.